Planar Anchoring of C70 Liquid Crystals Using a Covalent Organic Framework Template. Issue 45 (12th September 2019) - Cui, Daling; MacLeod, Jennifer M.; Rosei, Federico
Abstract: The surface‐induced anchoring effect is a well‐developed technique to control the growth of liquid crystals (LCs). Nevertheless, a defined nanometer‐scale template has never been used to induce the anchored growth of LCs with molecular building units. Scanning tunneling microscopy results at the solid/liquid interface reveal that a 2D covalent organic framework (COF‐1) can offer an anchoring effect to template C70 molecules into forming several LC mesophases, which cannot be obtained under other conditions. Through comparison with the C60 system, a stepwise breakdown in ordering of C70 LC is observed. The process is described in terms of the effects of molecular anisotropy on the epitaxial growth of molecular crystals. The results suggest that using a surface‐confined template to anchor the initial layer of LC molecules can be a modular and potentially broadly applicable approach for organizing molecular mesogens into LCs. Abstract : The elliptical molecule, C70, can only form structurally well‐defined crystals without an external templated effect. Through an introduction of anchored effect with covalent organic frameworks, several C70 mesophases are observed. The effects of C70 molecular anisotropy on the epitaxial growth of molecular crystals are understood by a stepwise breakdown in ordering in comparison to the C60 system.